THE EFFECT OF ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Mulyantoro, Anto; Silaningsih, Endang; Kartini, Tini (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The purpose of this study is to ascertain how organizational commitment and entrepreneurial orientation directly and mediating affect the performance of snack food Micro, Small, and Medium-Sized Enterprises (MSMEs) in South Bogor District.Methods: This study adopts a quantitative approach with a population consisting of all snack food MSME actors in the South Bogor area. The sample comprises 100 respondents, selected using a purposive sampling method within a non-probability sampling framework. Data were collected through questionnaires distributed directly to the respondents. The data analysis method used in this study combines descriptive and verification analysis, with path analysis employed to examine the relationships between the research variables.Results: The results showed that entrepreneurial orientation (X) and organizational commitment (Z) had a positive and significant effect on business performance (Y). In addition, organizational commitment (Z) is proven to significantly mediate the effect of entrepreneurial orientation (X) on business performance (Y). Keywords: Entrepreneurial Orientation, Organizational Commitment, Business Performance